Accrual accounting in government: Is fund accounting still relevant? - Salleh, Kalsom; Ab Aziz, Rozainun; Abu Bakar, Y. Nurli (Elsevier Ltd., 2014)
The main purpose of public sector accounting is to act as the trustee to protect and manage public moneys and discharge accountability.Fund Accounting is used as the rational response to serve as a reliable control technique for such purposes.With the emphasis of accrual accounting which is more reliable than cash accounting in measuring financial performance of government activities, this study therefore attempts to evaluate the relevance of the Fund Accounting in the planned adoption of accrual accounting by the Federal Government in Malaysia.Thus, the objective of this paper is to provide literature evidence to support on the relevance of Fund Accounting for the adoption of accrual basis of financial reporting in the Federal Government of Malaysia.